(untitled) (American Journal of Islam and Society, 1998)
The ambivalent relationship between Islam and modernity is a complex and fascinating subject into which Khoury delves with a seemingly good measure of sophistication. In this book of philosophical discourse, which he presents as a work of thought and only secondarily as an historical, scholarly, or descriptive effort, Khoury seeks to articulate a new and creative synthesis between both historical forces that ultimately would serve to recapture the illusive spirit of freedom in the Arab Muslim world. Khoury attributes the undermining of freedom in the Arab world to several reasons: the victory of orthodoxy and its ensuing ossification, with the result that no alternative to modernity, or even a synthesis, could be provided by Arab Muslim thinkers; the general shallowness of those who wage war against a trivialized modernity-a shallow Islam being the logical counterpart to a shallow modernism; habitual passivity in the face of despotism; and the continued insistence that Islam become intertwined with the modem state, which by its very nature and structure can only harm the implementation of Islam, at least as a project undertaken by the state (pp. xxiv-xxv, 3) ...